PERAN MANAJEMEN KESISWAAN DALAM MENCEGAH KENAKALAN SISWA DI SMP NEGERI 5 TAKALAR - Nurtiwi, Nurtiwi; Ridwan Idris; Alwan Suban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The research aims to analyze in depth the description of student management in preventing student delinquency at SMP Negeri 5 Takalar. In addition, this research is directed to identify various supporting and inhibiting factors that influence the effectiveness of student management, as well as to find strategic solutions in increasing the success of preventing student delinquency. This type of research is qualitative using descriptive analysis methods. The author specifically uses a phenomenological approach. Data were collected from primary sources, namely the principal, Vice Principal for Student Affairs, Guidance and Counseling Teachers, Parents and Students. Secondary data were collected directly from the research location through observation, interviews, and documentation. Data were analyzed through three stages: reduction, presentation, and drawing conclusions. Data validity was maintained by triangulation of sources and techniques. The results of the study show that: (1) Student management is implemented through planning an integrated coordination system, implementation through direct supervision and patrols of the school area for early detection of bullying, as well as synergistic evaluation between homeroom teachers, Guidance and Counseling teachers, and the principal. (2) Forms of student delinquency include administrative violations, time discipline (truancy), to serious violations of social norms such as verbal bullying. (3) The main supporting factors are collective commitment to the school's vision and clear regulations, while obstacles arise from the dynamics of impulsive student behavior. (4) The solution implemented uses a multidimensional approach that combines spiritual and psychological aspects, and intensive collaboration with parents to create sustainable behavioral changes. The results of this study provide important implications that include theoretical and practical aspects in the realm of educational management. Theoretically, this study emphasizes that the success of student character development is not sufficient to rely only on formal regulations, it requires a managerial approach that is humanistic, emotional, and spiritual.